Toward an anthropological look of flipped learning - Chambi Mescco, Edith (2019)
Defining the human being who education intends to form is a task of pedagogical anthropology, a labour that must be taking into account in order to be clear about the anthropological support of the educational practices carried out in the classroom which are often executed following instructions or experiences withoutthe necessary reflection of what is expected of the students and, therefore, of society. In this sense, it is important to analyse, from an anthropological point of view, one of the most popular pedagogical approaches for its favourable results: flipped learning. This approach aims to form a human being to buildknowledge based on autonomy and social interaction, promoting higher levels of knowledge that allow him to solve problems in his environment.